FEATURES OF 19th CENTURY LITERATURE: ROMANTICISM AND REALISM - Mamadkulova, Kamila (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article is devoted to the peculiarities of world literature of the 19th century, romanticism and realism. The topic of political and social changes, traditions in history and literature in the 19th century is also touched upon. Romanticism is an art born of a brief historical moment of uncertainty, crisis that accompanied the transition from a feudal system to a capitalist system; When by 1830 the outlines of capitalist society were determined, the art of realism replaced romanticism.